Answer:
Yes
Explanation:
5x + 2y = 17
We are given the values (1, 6)
Substitute then into the equation
(I put a question mark to basically ask the question “is 5(1) + 2(6) equal to 17?”)
5(1) + 2(6) = 17?
5 + 12 = 17?
Yes!
Hope this helped and made sense :)
Answer:
1295/36
Step-by-step explanation:
the statement tell us:
(7-(5/6))*(7-(7/6))
we have:
(7-(5/6))=((6*7)-5)/6=(42-5)/6=37/6
and we have:
(7-(7/6))=((6*7)-7)/6=(42-7)/6=35/6
we need multiply both terms:
(37/6)*(35/6)=(37*35)/(6*6)
finally we have
1295/36
Answer:
(4x3-6x) + (8x-12)= 2x
(4x3+8x) + (-6x2-12)= 2(2x-3) (x^2+2)
Step-by-step explanation:
All you have to do is simplify.
4x-4>20
Step 1: Add four to both sides
4x-4+4>20+4
4x>24
Step 2: Divide both sides by 4
4x divided by 4 and 24 divided by 4
Answer: x>6
Kahal accidentally subtracted instead of adding. He made a mistake in step 2.